Implementing the communication for development strategy to improve knowledge and coverage of measles vaccination in western Chinese immunization programs: a before-and-after evaluation - Ming Lu; Yao-Zhu Chu; Wen-Zhou Yu; Robert Scherpbier; Yu-Qing Zhou; Xu Zhu; Qi-Ru Su; Meng-Juan Duan; Xuan Zhang; Fu-Qiang Cui; Hua-Qing Wang; Yi-Biao Zhou; et al. (BMC, 2017)
Abstract Background Communication for Development (C4D) is a strategy promoted by the United Nations Children's Fund to foster positive and measurable changes at the individual, family, community, social, and policy levels of society. In western China, C4D activities have previously been conducted as part of province-level immunization programs. In this study, we evaluated the association of C4D with changes in parental knowledge of immunization services, measles disease, and measles vaccine, and changes in their children's measles vaccine coverage. Methods From April 2013 to April 2014, C4D activities were implemented as part of provincial immunization programs in the Inner Mongolia, Guangxi, Chongqing, Guizhou, Tibet, Shaanxi, Gansu, Ningxia, and Qinghai provinces. We used a before-and-after study design and employed face-to-face interviews to assess changes in parental knowledge and vaccination coverage. Results We surveyed 2 107 households at baseline and 2 070 households after 1 year of C4D activities. Following C4D, 95% of caregivers were aware of the vaccination record check requirement for entry into kindergarten and primary school; 80% of caregivers were aware that migrant children were eligible for free vaccination; more than 70% of caregivers knew that measles is a respiratory infectious disease; and 90% of caregivers knew the symptoms of measles. Caregivers' willingness to take their children to the clinic for vaccination increased from 51.3% at baseline to 67.4% in the post-C4D survey. Coverage of one-dose measles-containing vaccine (MCV) increased from 83.8% at baseline to 90.1% after C4D. One-dose MCV coverage was greater than 95% in the Guangxi, Shaanxi, and Gansu provinces. Two-dose MCV coverage increased from 68.5 to 77.6%. House-to-house communication was the most popular C4D activity among caregivers (91.6% favoring), followed by posters and educational talks (64.8 and 49.9% favoring). Conclusions C4D is associated with increased caregiver knowledge about measles, increased willingness to seek immunization services for their children, and increased measles vaccination coverage. Tailored communication strategies based on insights gained from these analyses may be able to increase vaccination coverage in hard-to-reach areas. C4D should be considered for larger scale implementation in China.